Public Debt and Economic Growth in Ghana. (March 2016) - Owusu‐Nantwi, Victor; Erickson, Christopher
Abstract: This study uses Johansen cointegration and the vector error correction model to examine the long‐term and causal relationship between public debt and economic growth in Ghana. Annual time series data were gathered from the World Bank Development Indicators and IMF Economic outlook data from 1970 to 2012. The findings from the study reveal a positive and statistically significant long‐run relationship between public debt and economic growth. Also, in the short run a bidirectional Granger causality link exists between public debt and economic growth. The study recommends that Ghana should acquire public debt for very high priority projects and programs that are well appraised and self‐sustained that could contribute positively to economic growth.